Knowledge on Respectful Maternity Care among Nurses in Selected Hospitals of Butwal Sub-Metropolitan City - Pandey, Sushma; Thapaliya, Rekha (NPRC Journal of Multidisciplinary Research, 2025)
Background: Respectful maternity care (RMC) ensures a positive birth experience. However, limited knowledge among nurses about RMC leads to higher rates of disrespect and abuse during childbirth. The study aimed to assess the level of knowledge on respectful maternity care among nurses.Methods: A descriptive cross-sectional study was conducted with 104 nurses working in selected hospitals in Butwal sub-metropolitan city. Non-probability, purposive sampling technique was used to select the hospitals, wards, and nurses. Data was collected using a self-administered structured questionnaire. The data was coded, entered into SPSS version 16, and analyzed using both descriptive and inferential statistics (Chi-square test).Results: The study showed that the mean age of the nurses was 31.19 ± 8.27 years. Among the 104 nurses, 60.5% had less than 10 years of work experience. Most of the nurses (73.1%) had completed PCL nursing, and 71.2% had previous experience in maternity wards. In terms of knowledge, 18.3% had adequate knowledge, 42.3% had moderate knowledge, and 39.4% had inadequate knowledge of respectful maternity care. There was no significant association between the level of knowledge on RMC and selected variables.Conclusion: The study concluded that nearly half of the nurses had a moderately adequate level of knowledge on respectful maternity care. Training and seminars on RMC should be held regularly to enhance nurses' knowledge of RMC.